"I just assume they don't know that I'm the doctor": Gender bias and professional identity development of women residents. Issue 2 (22nd March 2022) - Stavely, Taylor; Salhi, Bisan A.; Lall, Michelle D.; Zeidan, Amy
Abstract: Background: The increasing entry of women into medicine, a traditionally male‐gendered institution, has revealed much about the gendered politics of medical practice. Women are required to negotiate conflicting gender‐normative roles and expectations as they develop their professional identities. Relatively little is known with regard to the study of gender identity and professional development in emergency medicine (EM), with even fewer studies specifically examining women EM residents. Methods: This was a qualitative, semistructured interview study conducted at the Emory University Emergency Medicine Residency. Women residents in their first, second, and third years of training were recruited for participation through residency listservs. Interviews were completed using a virtual platform until thematic saturation was reached. Interviews were recorded, professionally transcribed, and coded by two study investigators. The study team met throughout the process to identify codes and themes from the interviews. Results: A total of 11 interviews were completed. Participants self‐identified as Black (five), White (two), biracial (two). and South Asian (two) and represented all levels of training. Participants identified challenges to providing clinical care and conveying their competency related to their gender and role as physicians in training. Common challenges included role confusion and questioning of their decisions by both patients and colleagues. They identified other aspects of their identity as facilitators for care delivery, specifically race as a facilitator when caring for race‐concordant patients. Participants described strategies developed to navigate gender‐specific challenges including routinely providing justification for their clinical decisions. Participants also described a need for interventions at the departmental and institutional levels to improve allyship and bystander behaviors. Conclusion: Women residents actively negotiate tensions between their gender and role as physicians and develop multifaceted strategies to address challenges in care delivery. Because residency training is a challenging yet formative time in developing one's professional identity, it is important to consider interventions that support women residents and the unique challenges they face.